Effectiveness of portable HEPA air cleaners on reducing indoor endotoxin, PM10, and coarse particulate matter in an agricultural cohort of children with asthma: A randomized intervention trial. (19th July 2021) - Riederer, Anne M.; Krenz, Jennifer E.; Tchong‐French, Maria I.; Torres, Elizabeth; Perez, Adriana; Younglove, Lisa R.; Jansen, Karen L.; Hardie, David C.; Farquhar, Stephanie A.; Sampson, Paul D.; Metwali, Nervana; Thorne, Peter S.; et al.
Abstract: We conducted a randomized trial of portable HEPA air cleaners in the homes of children age 6–12 years with asthma in the Yakima Valley, Washington. All families received asthma education while intervention families also received two HEPA cleaners (child's bedroom, living room). We collected 14‐day integrated samples of endotoxin in settled dust and PM10 and PM10‐2.5 in the air of the children's bedrooms at baseline and one‐year follow‐up, and used linear regression to compare follow‐up levels, adjusting for baseline. Seventy‐one families (36 HEPA, 35 control) completed the study. Baseline geometric mean (GSD) endotoxin loadings were 1565 (6.3) EU/m 2 and 2110 (4.9) EU/m 2, respectively, in HEPA vs. control homes while PM10 and PM10‐2.5 were 22.5 (1.9) μg/m 3 and 9.5 (2.9) μg/m 3, respectively, in HEPA homes, and 19.8 (1.8) μg/m 3 and 7.7 (2.0) μg/m 3, respectively, in control homes. At follow‐up, HEPA families had 46% lower (95% CI, 31%–57%) PM10 on average than control families, consistent with prior studies. In the best‐fit heterogeneous slopes model, HEPA families had 49% (95% CI, 6%–110%) and 89% lower (95% CI, 28%–177%) PM10‐2.5 at follow‐up, respectively, at 50th and 75th percentile baseline concentrations. Endotoxin loadings did not differ significantly at follow‐up (4% lower, HEPA homes; 95% CI, −87% to 50%).